Paul's discourse for the Corinthians' edification :a socio-rhetorical interpretation of 2 Corinthians 10-13 - Moon, Jang-Hwan (Stellenbosch : Stellenbosch University, 2011)
Thesis (DTh)--Stellenbosch University, 2004.